Nutrient accumulation in soils under long-term farm dairy effluent application : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Applied Science in Soil Science at Massey University, Palmerston North, New Zealand - Cox, Juliet (Massey University, 2005)
Land-based application of farm dairy effluent (FDE) has been encouraged by regional councils since the introduction of the resource management act (RMA) in 1991. The problems associated with FDE irrigation are high levels of nitrate in ground and surface waters which can lead to human health issues where the groundwater is used as drinking-water and environmental degradation of streams, rivers and lakes. Regional councils impose nitrogen loading limits to reduce the likelihood of environmental problems from nitrate leaching. Long-term data investigating FDE application and the associated soil changes over time is currently unavailable and the nutrient budgeting tool OVERSEER® Nutrient Budgets 2 is validated against only short-term trials. Therefore, assumptions made in the model for long-term FDE application areas may not be correct. The project investigated the soil chemical characteristics of six long-term (>6 years) farm dairy effluent paddocks and matched non-effluent paddocks in the Waikato and Bay of Plenty. Fieldwork involved the removal of five core samples from each paddock, with each core yielding six sub-samples of 75 mm depth. Soil analyses included bulk density calculations, cation exchange capacity, total carbon, nitrogen and phosphorus determination and Olsen P. It was found that two sites had the same total cation exchange capacity in the effluent and non-effluent paddocks, but the proportions of the individual cations were different. A significant (α = 0.05) difference in the exchangeable potassium concentration existed between the pairs of paddocks with much greater potassium found in the areas irrigated with FDE. No discernable difference in the concentrations of carbon and nitrogen was found between the topsoil of the effluent and non-effluent paddocks. This was due to the highly variable nature of the effluent and the soils themselves, and the large pool of nutrients in the soil, requiring a large change before a noticeable difference occurred. The total nitrogen and phosphorus levels found in the soil profiles (0-450 mm) of the effluent and non-effluent paddocks were very similar, and reflects the large additions of fertilisers to non-effluent paddocks. The OVERSEER® Nutrient Budgets model was used to produce nutrient budgets for farms from the Waikato and Bay of Plenty and predictions of accumulation of nutrients over time. Comparisons made between the OVERSEER® results and soil chemical analyses revealed that with the exception of potassium, it was not possible to accurately predict the nutrient concentration in the soil by extrapolation of OVERSEER® data. This was due to changes in management practices over time and the inherent variability of soils. If the model is to be used as a regulatory tool, accurate fertiliser records must be kept, along with frequent pasture and soil analysis. It is also advisable that a soil map of the farm area is completed in order to most accurately use the model.
Keywords: Dairy waste; New Zealand Dairy farms; Waste disposal; Soil fertility; Environmental aspects